Skeletal muscle functions around the clock. (September 2015) - Mayeuf‐Louchart, A.; Staels, B.; Duez, H.
Abstract : In mammals, the central clock localized in the central nervous system imposes a circadian rhythmicity to all organs. This is achieved thanks to a well‐conserved molecular clockwork, involving interactions between several transcription factors, whose pace is conveyed to peripheral tissues through neuronal and humoral signals. The molecular clock plays a key role in the control of numerous physiological processes and takes part in the regulation of metabolism and energy balance. Skeletal muscle is one of the peripheral organs whose function is under the control of the molecular clock. However, although skeletal muscle metabolism and performances display circadian rhythmicity, the role of the molecular clock in the skeletal muscle has remained unappreciated for years. Peripheral organs such as skeletal muscle, and the liver, among others, can be desynchronized from the central clock by external stimuli, such as feeding or exercise, which impose a new rhythm at the organism level. In this review, we discuss our current understanding of the clock in skeletal muscle circadian physiology, focusing on the control of myogenesis and skeletal muscle metabolism.